No time to lift? Designing time-efficient training programs for strength and hypertrophy: A narrative review - Iversen, V. M.; Norum, M.; Schoenfeld, B. J.; Fimland, M. S. (Sports Medicine, 2021)
Lack of time is among the more commonly reported barriers for abstention from exercise programs. The aim of this review was to determine how strength training can be most effectively carried out in a time-efficient manner by critically evaluating research on acute training variables, advanced training techniques, and the need for warm-up and stretching. When programming strength training for optimum time-efficiency we recommend prioritizing bilateral, multi-joint exercises that include full dynamic movements (i.e. both eccentric and concentric muscle actions), and to perform a minimum of one leg pressing exercise (e.g. squats), one upper-body pulling exercise (e.g. pull-up) and one upper-body pushing exercise (e.g. bench press). Exercises can be performed with machines and/or free weights based on training goals, availability, and personal preferences. Weekly training volume is more important than training frequency and we recommend performing a minimum of 4 weekly sets per muscle group using a 6-15 RM loading range (15-40 repetitions can be used if training is performed to volitional failure). Advanced training techniques, such as supersets, drop sets and rest-pause training roughly halves training time compared to traditional training, while maintaining training volume. However, these methods are probably better at inducing hypertrophy than muscular strength, and more research is needed on longitudinal training effects. Finally, we advise restricting the warm-up to exercise-specific warm-ups, and only prioritize stretching if the goal of training is to increase flexibility. This review shows how acute training variables can be manipulated, and how specific training techniques can be used to optimize the training response: time ratio in regard to improvements in strength and hypertrophy.